The First Year of the Medicare-DoD Subvention Demonstration Evaluation Report for FY 1999 - Farley, Donna O. (RAND Corporation, 2000)
In 1997, Congress directed the Health Care Financing Administration (HCFA) and the Department of Defense (DoD) to conduct a demonstration to test the feasibility of establishing Medicare managed care plans within the DoD TRICARE health benefits program for beneficiaries who are eligible for both DoD and Medicare health insurance coverage. The legislation was intended to expand access to military health care services for dually eligible beneficiaries while maintaining budget neutrality. This report focuses on one model being tested in the demonstration, called TRICARE Senior Prime. It presents the results of RAND's evaluation of the first year of operation at six demonstration sites.